2017
DOI: 10.15446/rfna.v70n1.61767
|View full text |Cite
|
Sign up to set email alerts
|

Production and composition of buffalo milk supplemented with agro industrial byproducts of the african palm

Abstract: The goal for this applied research was to assess the production and composition of buffalo milk when Oil Palm kernel flour and Oil Palm kernel cake are supplemented to their diet. Thirty buffaloes from the grasslands of the Andes valleys in Colombia with 1 to 3 lactations and an average weight of 575 kg were selected for the experimental. The animals were randomly assigned to one of three experimental groups: (T1 Control Group) with no diet supplements, (T2) 1000 g·day-1 of oil palm kernel cake and 350 g·day-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…In comparison to two other herds of Bulgarian Murrah under grazing conditions (Naydenova, 2005), results of this study concerning pasture farming (FM P ) showed that the most atherogenic C14:0 and the C12:0 are lower but C16:0 is higher, MUFA is lower but PUFA is definitely higher. Compared to studies in buffaloes under extensive conditions in Colombia (Bustamante et al, 2017) and…”
Section: Discussionmentioning
confidence: 97%
“…In comparison to two other herds of Bulgarian Murrah under grazing conditions (Naydenova, 2005), results of this study concerning pasture farming (FM P ) showed that the most atherogenic C14:0 and the C12:0 are lower but C16:0 is higher, MUFA is lower but PUFA is definitely higher. Compared to studies in buffaloes under extensive conditions in Colombia (Bustamante et al, 2017) and…”
Section: Discussionmentioning
confidence: 97%
“…Para el caso del PKC, Olafadehan y Adewumi (2009), en una investigación bajo condiciones de finca en pequeño productor suplementando vacas criollas en el este de Nigeria con 1,77 kg de suplemento que incluía 40 % de PKC, lograron incrementar de manera signicativa la producción de leche en 27,3 %, comparada con la dieta sin suplementación (2,28 vs. 1,79 kg/vaca/día, respectivamente). Asimismo, Bustamante et al (2017), suplementando con 1 kg de PKC más 0,35 kg de melaza de caña, incrementó signicativamente la producción diaria de leche en búfalos de agua (B. bubalis) al pasar de 2, 59 (sin suplementación) a 3,82 L/animal/día. La calidad composicional de la leche, en términos de grasa, proteína y sólidos totales, se vio afectada por el esquema de suplementación tanto en el experimento i como en el ii.…”
Section: Resultados Y Discusiónunclassified
“…Con base en los subproductos torta de palmiste (PKC) y decantado de euentes (OPDC), se generaron dos dietas experimentales que se compararon con una dieta control (suplementación mineral al 8 % de fósforo). Cada una de las dietas experimentales contó con participación de los subproductos de la palma de aceite y la adición de una fuente energética (melaza de caña), según lo recomendado por Bustamante et al (2017) y Zahari et al (2012), así como también una fuente de NNP (úrea) y de azufre (sulfato de amonio) (tabla 1). A cada animal se le suministró diariamente 200 g de sal mineralizada y 1.782 g de las dietas experimentales (PKC y OPDC).…”
Section: Dietas Selección De Animales Y Diseño Experimentalunclassified
See 1 more Smart Citation
“…Diversas investigaciones han evaluado el efecto de la suplementación proteica, energética y lipídica en los búfalos (Santillo et al, 2016;Bustamante et al, 2017;Naveed-ul-Haque et al, 2018). Sin embargo, en las condiciones tropicales de México no existe información acerca de su utilización en la especie bufalina.…”
Section: Introductionunclassified